Widger's Quotes and Images from Conscience by Hector Malot : The French Immortals: Quotes and Images - Malot, Hector, 1830-1907; Widger, David, 1932-2021? (Salt Lake City, UT : Project Gutenberg, 2009)
"Widger's Quotes and Images from Conscience" by Hector Malot is a collection of thought-provoking quotes and reflections, likely written during the late 19th century. The book explores intricate concepts related to conscience, self-awareness, and the human experience, presenting various aphorisms that delve into philosophical and moral dilemmas. In this concise yet impactful compilation, Malot presents a series of quotations that reflect on the nuances of conscience and its influence on human behavior. Through a variety of perspectives, he examines themes such as the relationship between luck and effort, the complexities of self-judgment, and the idea that personal circumstances shape one$1 (Bs moral compass. The quotes suggest that one's conscience is often clouded by environmental factors and education, emphasizing the significant role they play in shaping our thoughts and actions. Malot's work invites readers to contemplate their own values and the motivations behind their decisions, offering insights into the human condition. (This is an automatically generated summary.)s
Release date is 2009-07-13
This eBook was produced by David Widger
Keywords: Quotations, French -- Translations into English